WHAT IS PERCEPTION, KNOWLEDGE AND RELIGIOUSITY ON INTEREST IN SAVING AND THE DECISION TO BECOME A BSI CUSTOMER? - Tahtiar, Nizariafin Hifni; Juliana Jaya, Tiara J (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to test and analyze the influence of perspective, public knowledge, and religiosity on the interest in saving for Bank Syariah Indonesia (BSI) customers in Malang City. The research approach used is quantitative research. The sampling technique in this research uses a non-probability technique with a purposive sampling method. The required sample is 385 respondents who are Bank Syariah Indonesia (BSI) customers aged 17 years and over and domiciled in Malang City. The primary and secondary data used in this research are primary and secondary data. Data analysis in this research uses analytical tools like SMART PLS version 3.0 which aims to calculate statistical values such as data quality testing and hypothesis testing. The results of this research show that perspective (X1) has a positive and significant influence on interest in saving (Z), public knowledge (X2) has a positive and significant influence on interest in saving (Z), religiosity (X3) does not have a significant influence on interest in saving (Z), Interest (Z) has a positive and significant influence on saving decisions (Y). Perspective (X1) has a positive and significant influence on the decision (Y) through interest, public knowledge (X2) has a positive and significant influence on the decision to save (Y) through interest (Z), religiosity does not have a significant influence on the decision to save (Y) through interest (Z).